Examining the Impact of Financial Distress, Tax Justice, Sustainable and Ethical Leadership on Tax Compliance - Sri Utami Nurhasanah; Sarah Fitriyani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research aims to investigate the interplay between financial distress, tax justice, sustainable and ethical leadership, and their impact on tax compliance. The study employs a theoretical framework integrating principles of financial management, justice theory, and leadership ethics. A purposive sampling technique will be utilized to select participants from diverse organizational backgrounds, including corporations and non-profit entities. Data will be collected through in-depth interviews and thematic analysis will be employed to analyze the qualitative data. Preliminary findings suggest that financial distress exacerbates tax compliance challenges, while ethical leadership and a fair tax system positively influence compliance behavior. The study contributes to understanding the complex dynamics shaping tax compliance and provides insights for policymakers and organizational leaders to enhance compliance practices.